Cyborgs@cyberspace? : an ethnographer looks to the future - Hakken, David (Routledge, 1999)
Cyborgs@Cyberspace? is a compelling and innovative analysis of technology from a cultural perspective. It turns an anthropological eye on the growing phenomenon of cyberspace to address some of the pressing questions of the Computer Age: How significant are the social practices which emerge from our increasing use of advanced information technology? Are the cultural infrastructures of cyberspace destined to be the primary arena of human activity in the future? And what are the possibilities and dangers that arise from our use and misuse of computer culture? Arguing that humans have always been technological as well as cultural beings, David Hakken calls for a fundamental rethinking of the traditional separation of anthropology and technical studies. Drawing on three decades of research on contemporary technological societies, this book outlines a fresh way of thinking about technology and offers an ethical and political response to the challenge of truly living as "cyborgs" in the age of cyberspace.